Commentary to Skudlik et al. (2023): why a scoping review and why only Germany? - Bich-Lien Nguyen (BMC, 2024)
Abstract This letter to the editor is a commentary on the scoping review by Skudlik et al. (2023) on the relocation of older people to nursing homes in Germany. In this commentary, we question certain methodological decisions that, in our view, particularly affect transferability of the results and give a partial picture of the phenomena studied by limiting the inclusion to German studies. We also have questions about the choice of knowledge synthesis method and why the concept of "nursing home" was not defined. We hope that this letter will open a constructive scientific discussion on an important topic that is understudied as the world's population ages.